Expressing Confidence in Unions in Quebec and the Other Canadian Provinces: Similarities and Contrasts in Findings - Frangi, Lorenzo; Hennebert, Marc-Antonin (Relations industrielles / Industrial Relations, 2015)
This article examines changes in levels of confidence in unions and proposes an intra-national comparison between Quebec and the rest of Canada based on the analysis of the three most recent waves of the World Values Survey (WVS) database, of which Canada is part (i.e. 1990, 2000, 2006). After noting differences in the trends of confidence in unions in these two regions, we applied the same logistic regression model to both regions, based on the 2006 WVS wave, in order to bring out the determinants of the propensity of individuals to express confidence in unions. The results show both similarities and differences between the two regions. As for the similarities between Quebec and the rest of Canada, it should be noted that involvement in politics and the fact of being unionized had a positive effect on the respondents’ propensity to have confidence in unions whereas most of the socio-demographic variables had no significant effects. As for the differences, the fact of reporting a higher income had a significant negative impact in Quebec, but was not significant in the rest of Canada. The fact of supporting the NDP in the rest of Canada had a more structuring effect on the propensity of individuals to have confidence in unions than the fact of supporting the BQ in Quebec. Moreover, the greater the extent to which citizens in Quebec identified with left-leaning ideological positions, the more likely they were to have confidence in unions. Finally, the respondent’s level of education was not significant in the rest of Canada but, cetiris paribus, was highly significant and positively related to confidence in unions in Quebec.